Performance of rainfed Persian lime cv. BRS EECB IAC Ponta Firme on 26 rootstocks under Aw climate - Silva, Larissa Nunes [UNESP]; Vitória, Marina Ferreira [UNESP]; Moreira, Alécio Souza; Girardi, Eduardo Augusto; Stuchi, Eduardo Sanches (FapUNIFESP (SciELO), 2023)
It is necessary to diversify the scion/rootstock combinations for Persian lime cultivation, notably under tropical rainfed conditions. Therefore, in this work we evaluated the performance of a new cultivar, BRS EECB IAC Ponta Firme, up to six years after planting on 26 citrus rootstocks under Aw climate in northern São Paulo state, Brazil. Thirty single-tree randomized replications of each rootstock were evaluated without irrigation at 1,000 trees·ha-1. Lemon-type, followed by mandarin rootstocks induced the largest tree size and higher mean yield, probably related to the higher drought tolerance. The true dwarfing rootstocks of Flying Dragon trifoliate orange and Lindcove citrandarin were highly drought-intolerant, but, in addition to Swingle citrumelo and four other citrandarins, they did not present huanglongbing-symptomatic trees during the evaluation period under strict control of the insect vector. Overall, BRS EECB IAC Ponta Firme fruit quality was minimally influenced by the rootstock cultivar and fulfilled the requirements for both domestic and export fresh fruit markets. Due to superior production efficiency associated with high yield in relation to the canopy size, the Goutoucheng sour orange, BRS Ary, BRS Bravo and BRS Matta hybrids were selected as potential rootstocks of rainfed BRS EECB IAC Ponta Firme lime under Aw climate (tropical savannah) conditions.
Keywords: Citrus × latifolia; drought tolerance; essential oil; graft compatibility; huanglongbing; yield